Islam, Modern Scientific Discourse, and Cultural Modernity - Ahmad Fouad Basha (International Institute of Islamic Thought, 1992)
Thank you for sending me Bassan Tibi’s paper, entitled “Islam, Modern Scientific Discourse and Cultural Modernity: The Politics of Islamization of Knowledge as a Claim to Dewesternization,” which was presented at the 1990 MESA conference. I read it with great interest and would like to make the following observations. The main focus of this paper is the presentation of a critique of the Islamization of scientific thought adopted by contemporary Muslim intellectuals, with special attention paid to its reliability for the establishment of an authentic Islamic sociology. A comparison is made with the so-called European project of cultural modernity, a project based on the purely secular concept of knowledge. While engaging in this comparison, Tibi raises a number of issues that are strongly related to the influence of various partial truths and secular ideological perspectives prevalent in the modern West. However, in his methodological approach, the author is basically ignoring, either consciously or otherwise, the viewpoint of history and the philosophy of human civilization. These factors dictated my choice of the following three points for discussion. The first point relates to the so-called “Weberian demagnification of the world,” a concept developed in Europe during the seventeenth century that rests on the modern understanding of objectivity in the sciences. However, this statement is completely false, for the earliest claim of demagnification of the world dates back to the emergence of Islam. The first divine command from Allah to His Prophet Muhammad and to all humanity was: Read in the name of your Lord, the Creator . . . Read, for your Lord is the most gracious. He taught the art of writing. He taught man what man never knew before (Qur’an 96:1, 3-5). Many other Qur’anic and prophetic texts prompt Muslims to accumulate positive knowledge and to make the acquisition of scientific comprehension part of the community’s life. The Qur‘an emphasizes the superiority of scientists ...